Motivational determinants and their influence on the performance of elite athletes: An integrative review (Research, Society and Development, 2025)
This integrative review (2020-2025) investigated the main motivational determinants affecting the performance of elite athletes, utilizing the PRISMA-P 2020 methodology. The goal was to provide a scientific basis for psychological interventions in high-performance sport. Fourteen original articles and reviews across various sports were analyzed. The results confirmed that intrinsic motivation and autonomous motivational quality are crucial for resilience, adherence, and performance consistency. Task-oriented motivational climates and coaching styles that support basic psychological needs (autonomy, competence, and relatedness) were positively associated with well-being and engagement. In contrast, ego-oriented environments and excessive pressures increased the risk of burnout and competitive anxiety. Self-efficacy, openness to experience, and metacognitive skills (planning, reflection), mediated by intrinsic motivation, explained a significant portion of the variation in performance. The discussion suggests that interventions based on Self-Determination Theory and the creation of mastery climates are effective for optimizing sustainable results. The balance between intrinsic motivation and well-applied extrinsic incentives can potentiate performance without undermining the athlete's autonomy. Future studies should focus on longitudinal analyses that integrate motivational variables, mental health, and physiological indicators, also considering cultural differences, gender, and the context of parasports.